2013
DOI: 10.1089/hum.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Therapeutic Effects Conferred by an Experimental DNA Vaccine Targeting Human Papillomavirus-Induced Tumors

Abstract: Human papillomavirus (HPV) infection is responsible for all cervical cancer cases, other anogenital cancers, and head and neck tumors. The epidemiological relevance of HPV-induced tumors reinforces the need for the development of therapeutic antitumor vaccines. Clinical trials with different vaccine formulations, particularly DNA vaccines, have provided promising results but have still been unable to achieve the immunogenicity required for use in infected patients. In experimental conditions, anticancer HPV-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
2
25
0
9
Order By: Relevance
“…The DNA vaccine encoding the HPV-16 E7 protein genetically fused after amino acid 244 of the HSV-1 gD protein has been described previously (21,23). The gene sequence encoding the gDE7 chimeric protein was cloned into the pVAX1 vector (Invitrogen), which contains a cytomegalovirus (CMV) promoter and a kanamycin resistance gene.…”
Section: Dna Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA vaccine encoding the HPV-16 E7 protein genetically fused after amino acid 244 of the HSV-1 gD protein has been described previously (21,23). The gene sequence encoding the gDE7 chimeric protein was cloned into the pVAX1 vector (Invitrogen), which contains a cytomegalovirus (CMV) promoter and a kanamycin resistance gene.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…We previously showed that the coadministration of a plasmid encoding IL2 with a DNA vaccine encoding the HPV-16 E7 protein genetically fused to HSV-1 gD (pgDE7) generated full therapeutic antitumor protection after a single vaccine dose (21). In contrast, under the same conditions, immunization with the vaccine vector without coadministration of the plasmid encoding IL2 resulted in the activation of similar numbers of E7-specific CD8 þ T cells but did not confer therapeutic antitumor protection.…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other delivery vectors for E6 and E7 peptides include Semliki Forest virus (combined with low‐dose irradiation) , Listeria , lentiviruses , fusions with heat shock proteins , ricin B chain , Shiga toxin B subunit and synthetic polymers . Several studies have examined E6 or E7 DNA vaccines combined with various adjuvants . Immunization of mice with a mixture of DNA expressing E6/E7 and IL‐33 was able to induce regression of a transplantable HPVE6/E7‐expressing tumour and generate memory CD8 T cells while an E7 DNA vaccine combined with cyclophosphamide (to reduce regulatory T cells) produced potent anti‐tumour responses .…”
Section: Therapeutic Vaccinesmentioning
confidence: 99%
“…Among some of these properties, it is worth mentioning that: i-cruzipain is expressed in all developmental stages and strains of the parasite 10 ; ii-it is accumulated in the lysosomes, it is secreted and also present at surface level, being able to hydrolyze immunoglobulins 11 ; iii-it plays an important role in the process of internalization within mammalian cells 12 ; and iv-it is highly immunogenic in natural infection. 13 Recent improvements to DNA vaccines and the potential and flexibility of DNA as a potent immunization strategy for inducing both humoral and cell-mediated immune responses, make them an ideal therapeutic approach for treating or eliminating chronic disease, as it was shown in multiple sclerosis, 14 human papillomavirus, 15,16 hepatitis B 17 , human immunodeficiency virus, 18,19 simian immunodeficiency virus, 20 Mycobacterium tuberculosis, 21 Leishmania spp., 22,23 Schistosoma mansoni, 24 as well as against T. cruzi. 25,26 We have previously reported the efficacy of attenuated Salmonella enterica (S) carrying plasmid encoding cruzipain (SCz) to protect against T. cruzi infection.…”
Section: Introductionmentioning
confidence: 99%